ISLAM SEBAGAI ALTERNATIF PARADIGMA DAN EPISTEMOLOGI ILMU PENGETAHUAN - Muhammad Dudi Hari Saputra (JURNAL AL-AQIDAH, 2022)
AbstractThis paper tries to introduce Islam as an alternative paradigm and epistemology perspective in contemporary science profoundly and mitigate or tackle the perplexing problems between Western civilization and Islamic civilization. Firstly, this paper emphasizes the brief anomaly condition of the western knowledge system internally. Secondly, this paper shows a critical analysis of the Islam paradigm internally and externally (to western system knowledge). Thirdly, this paper aims to expound on alternative knowledge problem solutions and intellectual ethos by Islam (Exotericism and Esotericism). Fourthly, Assessment of Islam paradigm toward West paradigm as a clash of harmony regarding the modern and postmodern world. And lastly conclusion of the paper.